Green spaces and the impact on cognitive frailty: a scoping review - Fowler Davis, Sally; Benkowitz, Charlotte; Nield, Lucie; Dayson, Chris (Frontiers in Public Health, 2024)
Some literature indicates that contact with green spaces can benefit health and wellbeing, but it is unclear whether this is protective of cognitive health in older people. Using Arskey and O'Malley's framework the aim was to investigate ageing, cognitive frailty and the effects of green access including any causality. The evidence was somewhat inconsistent but suggestive for a beneficial role of green space exposure on cognitive functions. Results suggested that globally, the poorer urban environments are high risk for older people's mental health and these places often lack parks and green spaces. There is evidence that the level of activity and social participation may be greater with access to green spaces and therefore reduces health risks. Green spaces seem to have a role in preventing cognitive frailty, especially for more vulnerable older populations living in poorer urban environments.